ANALISIS TARGET COSTING SEBAGAI SARANA PENGENDALIAN BIAYA PRODUKSI PADA UKM BROSEM KOTA BATU - Dwi Kusuma Indiarti (Universitas Gajayana Malang, 2019)
Abstract: Target costing is the determination of the maximum possible cost for the manufacture of a product and then designing a profitable prototype with the maximum cost constraints that have been set. The purpose of this research is to find out how the implementation of target costing in controlling production costs in UKM Brosem. This research method is a case study. The type of research used is quantitative descriptive. The object of this research is the UKM Brosem in Batu City. The results of research using target costing through the value engineering process in UKM Brosem is able to reduce production costs by replacing apple raw material suppliers. Through this process, the company can save production costs of Rp. 382 / cardboard. The efficiency of production costs is the difference between company calculations and calculations using target costing. Keywords: target costing, production costs, production cost efficiency